Gaps in Knowledge About SARS-CoV-2 & COVID-19 Among University Students Are Associated With Negative Attitudes Toward People With COVID-19: A Cross-Sectional Study in Cyprus - Nicos Middleton; Constantinos Tsioutis; Ourania Kolokotroni; Alexandros Heraclides; Panagiotis Theodosis-Nobelos; Ioannis Mamais; Maria Pantelidou; Dimitrios Tsaltas; Eirini Christaki; Georgios Nikolopoulos; Nikolas Dietis (Frontiers Media S.A., 2021)
University students represent a highly active group in terms of their social activity in the community and in the propagation of information on social media. We aimed to map the knowledge, attitudes, and perceptions of University students in Cyprus about severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and Coronavirus disease 2019 (COVID-19) to guide targeted future measures and information campaigns. We used a cross-sectional online survey targeting all students in conventional, not distance-learning, programs in five major universities in the Republic of Cyprus. Students were invited to participate through the respective Studies and Student Welfare Office of each institution. The survey was made available in English and Greek on REDCap. Participation was voluntary and anonymous. The questionnaire was developed based on a consensus to cover the main factual information directed by official channels toward the general public in Cyprus at the time of the survey. In addition to sociodemographic information (N = 8), the self-administered questionnaire consisted of 19 questions, assessing the knowledge regarding the characteristics of SARS-CoV-2 and COVID-19, infection prevention and control measures (N = 10), perceptions related to COVID-19, for instance, whether strict travel measures are necessary (N = 4), and attitudes toward a hypothetical person infected (N = 2). Furthermore, participants were asked to provide their own assessment of their knowledge about COVID-19 and specifically with regard to the main symptoms and ways of transmission (N = 3). The number of students who completed the survey was 3,641 (41% studying Health/Life Sciences). Amongst them, 68.8% responded correctly to at least 60% of knowledge-related questions. Misconceptions were identified in 30%. Only 29.1% expressed a positive attitude toward a hypothetical person with COVID-19 without projecting judgment (9.2%) or blame (38%). Odds of expressing a positive attitude increased by 18% (95% CI 13-24%; p < 0.001) per unit increase in knowledge. Postgraduate level education was predictive of better knowledge (odds ratio (OR) 1.81; 95% CI 1.34-2.46; p < 0.001 among doctoral students] and positive attitude [OR 1.35; 95% CI 1.01-1.80; p = 0.04). In this study, we show that specific knowledge gaps and misconceptions exist among University students about SARS-CoV-2 and COVID-19 and their prevalence is associated with negative attitudes toward people with COVID-19. Our findings highlight the integrated nature of knowledge and attitude and suggest that improvements to the former could contribute to improvements in the latter.